Temporal variability of physico-chemical properties of St. Naum karst springs feeding Lake Ohrid - Jordanoska, Biljana; Kunz, Manuel; Stafilov, Trajče; Wüest, Alfred (Macedonian Journal of Ecology and Environment, 2010)
Lake Ohrid is strongly affected by karstic springs. Sub-aquatic as well as surface springs provide 27% to the overall water input of 38 m3 s-1. This particularity of cool, clean and oxygen-rich inflowing water was an important prerequisite for the establishment of the extraordinary biodiversity of Lake Ohrid. The aim of this article is to present physico-chemical properties of the spring water located in the southern part of the lake. Eight individual springs, belonging to the larger spring complex of St. Naum, were monitored for three years. The first part of the data record revealed long-term stability of spring water characteristics. The water temperature remained constant with variability of only 0.1 °C to 0.2 °C. Similarly, small changes in electrical conductivity, pH, dissolved oxygen and stable isotopes emphasize the low variability of the water properties. In turn, a comparison of the datasets reveals substantial differences between the eight springs in spite of their close proximity to each other. Temporal stability and spatial heterogeneity of the water properties suggest the existence of a complex and voluminous groundwater system feeding the springs, in which the spring waters are expected to be stored in large reservoirs for a long period of time. These observations imply that changes in the Lake Ohrid spring water quality may take effect with a substantial delay relative to alterations in its catchment.